Analysis of Sea Transportation Services in Pulau Banyak, Aceh Singkil Using a Qualitative Approach: Analisis Layanan Transportasi Laut di Pulau Banyak Aceh Singkil Menggunakan Pendekatan Kualitatif - Taharuddin; Kurniadi, Dedy; David, Muhammad; Siregar, Muhammad Sapril; T. M. Jamil; Sultan (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2024)
Island communities such as Banyak Island use sea transportation services as the main means of mobilization, both for work and as support to places that cannot be served by land vehicles. In addition to the local community, sea transportation services are also needed by tourists who will visit the area. This is because sea transportation is the only means that can be used to get to the island area. Currently, companies that provide sea transportation services on the Singkil mainland to Banyak Island are river, lake, and crossing transportation (ASDP) and wooden fishing boats seen pay which the island community has used for generations, and there are also fast boats that operate occasionally. The purpose of this study is to determine the condition of the availability of sea transportation for community needs fulfillment services in Aceh Singkil and Banyak Island, in addition to assessing the use of the system dynamics model with sea transportation services in Aceh Singkil and Banyak Island, and to assess the effect of sea transportation services on the economic level of the people of Aceh Singkil and Pulau Banyak. The method used in this study is a qualitative approach method. The results obtained from this study are: 1) The availability of sea transportation facilities in the future needs to be accelerated by increasing the number of sea transportation facilities serving the Singkil mainland and Banyak Island along with the increasing number of residents and visitors from within and outside the country as tourists; 2) Sea transportation services operating on Banyak Island provide a positive contribution to the local economy; and 3) To maintain the quality of sea transportation services, it is necessary to improve the existing sea transportation facilities and infrastructure.